Global research trends on immunotherapy in cancer: A bibliometric analysis - Zhichao Yao; Zhiyong Lin; Weijia Wu (Taylor & Francis Group, 2023)
Cancer immunotherapy has been gradually introduced and has undergone noteworthy developments in recent years. The number of scientific publications has been expanding, and the progression in this field has been rapidly evolving with time. This study aimed to use bibliometric analysis to examine the past 20 years of research on cancer immunotherapy and identify future hotspots. A literature search for medical publications on immunotherapy in cancer from 2000 to 2021 was conducted in the Web of Science Core Collection on March 1, 2022. Visualization analysis was performed using VOSviewer software (version 1.6.16). From 2000 to 2021, a total of 18,778 publications were retrieved. Annual publication output grew rapidly from 366 in 2000 to 3,194 in 2021. The USA issued the largest number of publications (n = 6,739, 35.89%), with the University of Texas System making the largest contribution (n = 802, 4.27%). A total of 976 meaningful topics were identified and further classified into 4 different clusters (immune mechanism, cancer biology, immunotherapy and clinical trials). The most common research topics included 'expression', 'chemotherapy', 'dendritic cells', 'pembrolizumab' and 'open-label'. Highly identified cancer types included hepatocellular, bladder, breast and lung cancer. A shift in popularity from mechanism research to clinical trials was observed, indicating that clinical application would be the center of attention in the future. Attention has been given to the field of cancer immunotherapy, and this trend will continue in the future. This study provides an unbiased visualization analysis on this topic in a scale-efficient manner for further research.